The Development of Gas Ordering and Delivery Application for Chuan Huat LPG Sdn. Bhd - Azlin, Nur Aina Najwa; Aman, Hannani (Applied Information Technology And Computer Science, 2022)
Gas ordering and delivery application is a user-friendly application that help Chuan Huat Company in organizing their order record and delivery process to run smoothly. When a consumer place a gas order thru call to chuan huat company, usually consumer expect to receive their order as soon as possible.  But in the company side, they may have occurred some kind of obstacle such as their worker not available, their stock running out or else. Therefore, it such a problem when consumer does not know when their order will be received at home. This application could help customer to track their order. Other than that, the company can make prediction on the gas demand and lowering the risk for losing the invoice during delivery. The target user in this project are customer, seller and staff. The module for customer is Login, Register, Profile, Order, Order List, and Order History. While for the seller, the module are Login, Staff Record, Order Record, and Customer Record. The staff have Registration, Login, Profile, Task, Task List, and Task History as module. The system process model use for this proposed system is structured approach. This application is using android technology and available for android user only. The programming language are JAVA as the front end is using Android Studio. While the database is using Firebase Firestore. This application is expected to make the ordering process becoming easier for the customer. The seller can easily manage the order record in systematic way. Moreover, this application helps the staff in organizing their task so that enhance their performance. Overall, this application will help Chuan Huat Company in improving their existing system and give a new business environment that is more systematic.